SPATIAL ANALYSIS AND LOCATION SELECTION FACTORS SHOPPING CENTER IN BEKASI CITY - L. Cahya, Darmawan; Nurul Srigati, Dinanda; Novetriska Putri, Mega; Haizam Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Development of shopping centers is uneven in Bekasi City. This causes sub-districts without shopping centers to come to the center of Bekasi City to come to entertainment or recreation centers such as shopping centers. This study aims to discuss the spatial analysis of distribution patterns and factors in selecting the location of shopping centers in Bekasi City. The research method used is quantitative descriptive by using the nearest neighbor analysis for distribution patterns, and weighting analysis by calculating the average (mean) for the shopping center location selection factor. The results showed that the distribution pattern of shopping centers in Bekasi City tends to be in groups located in the city center. Factors that determine the location of shopping centers in Bekasi City are influential factors are accessibility factors, demographic factors, consumer socio-economic factors, psychographic factors and competition factors.